2020
DOI: 10.37762/jgmds.7-1.100
|View full text |Cite
|
Sign up to set email alerts
|

Pre and Post-Operative Dental Pain and Anxiety in Patients Undergoing Routine Dental Extraction, Peshawar

Abstract: OBJECTIVES: To determine the pre and post-operative dental pain intensity and dental anxiety in patients undergoing tooth extraction and providing counselling with dental treatments.  METHODOLOGY: It was a comparative study conducted in dental hospitals of Peshawar i.e. Sardar Begum Dental College and Khyber College of Dentistry. A total of 200 participants were selected for this study through simple random sampling technique. Half of the participants (N=100) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Vargas R et al found a positive predictive value of 48% for the diagnosis of molar pregnancy. 16 Previous studies have only looked at cases where the diagnosis of a molar pregnancy was made histologically to give an estimate of sensitivity. It would be interesting to see whether our data are replicated in other units with a dierent clinical set ups, stang and degrees of supervision, to see whether this pattern of diagnosis is consistent across modern practice.…”
Section: Discussionmentioning
confidence: 99%
“…Vargas R et al found a positive predictive value of 48% for the diagnosis of molar pregnancy. 16 Previous studies have only looked at cases where the diagnosis of a molar pregnancy was made histologically to give an estimate of sensitivity. It would be interesting to see whether our data are replicated in other units with a dierent clinical set ups, stang and degrees of supervision, to see whether this pattern of diagnosis is consistent across modern practice.…”
Section: Discussionmentioning
confidence: 99%